Short Term HIIT increase VO2max, but can’t decrease Free Fatty Acids in Women Sedentary Lifestyle - Fajar Syamsudin; Lilik Herawati; Ema Qurnianingsih; Rias Gesang Kinanti; Gosy Endra Vigriawan; Eka Arum Cahyaningrum; Muchammad Rif'at Fawaid As'ad; Cyuzuzo Callixte (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Previous studies have investigated the effects of high-intensity interval training (HIIT) on cardiorespiratory fitness and body composition in overweight populations. However, short-term effect of HIIT and free fatty acids (FFA) serum in women sedentary lifestyle is not clearly understood. The aim of this study was to investigate the effect of 2-week high intensity interval training on body fat percentage, free fatty acids, and VO2max in overweight sedentary adult women. The fourteen sedentary young women (18–30 years old) randomly divided to control and HIIT groups. The HIIT group performed two-weeks training program, 20 min of repeated 10 s cycling interspersed with 50 s rest intervals per session, four days in a week. The variables were taken before and after intervention. The result showed the VO2max improved significantly (p<0.05)  and the change of body fat percentage was decreased significantly (p<0.05) in HIIT compared to control. The FFA levels were raised in HIIT and reduced in control, but they were not significantly different between groups (p≥0.05). The conclusion of this study reveals that the HIIT can be a reliable strategy for countering obesity in the adult population for improving fitness level and lessen body fat percentage. It may cause by increase energy metabolism. However, its underlying mechanism seem not via FFA. Then the further study needs to be conducted to figure out the other metabolic subtances in human body.